(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In our literary studies, the novella as a separate genre has not yet found its scientific and theoretical basis. In fact, it is not a question of which genre the works of art belong to, but of giving them a correct assessment based on the achievements of today’s literary studies. The article analyzes two works written in this genre in Japanese and Uzbek literature, their common and different aspects are revealed.